Efek Pemberian Kefir Susu Kambing Madu pada Gambaran Histopatologi Pankreas dan Fungsi Ginjal pada Tikus Diabetes: Effects of Honey Goat Milk Kefir on Pancreatic Histopathology and Renal Function in Diabetic Rats - Mulyadewi, Amelia Luthfiyah; Ilmi, Ibnu Malkan Bakhrul; Hardiansyah, Angga (Universitas Airlangga, 2024)
Background: The prevalence of diabetes is rising. Chronic metabolic disease type 2 diabetes may damage renal function and harm the pancreas. One of the initiatives to prevent and manage type 2 diabetes through functional foods. The antidiabetic and antioxidant properties of goat milk kefir with honey are thought to help heal kidney and pancreatic damage. Objectives: Evaluating the effects of feading fermented goat milk with honey on pancreatic histopathology and renal function in diabetic rats. Methods: A true experimental study conducted on 42 male Sprague-Dawley rats aged 6-8 weeks were divided into Six groups: Healthy Rats (KS); DM Rats (KN); quercetin (K1); metformin (K2); Kefir (P1); Preventive (P2). Diabetic rats type 2 were conditioned by HFD and injecting streptozotocin. Oral kefir was given 1.8 ml/200g BW/day for 21 days to groups KK and KP. Renal function was analyzed with pre-post tests through measurement of serum levels urea and creatinine, while the histopathological features were evaluated at the end of the study. The Kruskal-Wallis and post hoc Mann-Whitney test are used to analyze the data. Results: P1 rats had Creatinine level of 0.57 ± 0.07 mg/dL; BUN 27.56 ± 6.22 mg/dL; Beta Cell Count 104.2; Island Area of Langerhans 170.26. The levels of BUN (p-value=0.083), creatinine (p-value=0.016), and Langerhans island area (p-value=0.026). Creatinine of rat P1 were significantly different from KN (p-value<0.05). Conclusions: Goat milk kefir with honey in type 2 diabetic rats show beneficial effects on serum BUN, creatinine, and histopathological features of the pancreas as treated with metformin.